2008
DOI: 10.1063/1.2838234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mechanical stress on gate tunneling currents of germanium and silicon p-type metal-oxide-semiconductor field-effect transistors and metal gate work function

Abstract: Articles you may be interested inFluorine implantation for effective work function control in p -type metal-oxide-semiconductor high-k metal gate stacks J. Vac. Sci. Technol. B 29, 01A905 (2011); 10.1116/1.3521471 Low temperature mobility in hafnium-oxide gated germanium p -channel metal-oxide-semiconductor field-effect transistors Appl. Phys. Lett. 91, 263512 (2007); 10.1063/1.2828134 Physics of strain effects in semiconductors and metal-oxide-semiconductor field-effect transistors Strain-induced changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…7(b-c)). This is in line with previous observations by Choi et al on the reduction in the work function of TiN due to tensile out-of-plane bending which reduces the Gate/Oxide barrier height causing higher leakage currents [17].…”
Section: B Effect Of Bending Axis Orientation Stress Typesupporting
confidence: 82%
“…7(b-c)). This is in line with previous observations by Choi et al on the reduction in the work function of TiN due to tensile out-of-plane bending which reduces the Gate/Oxide barrier height causing higher leakage currents [17].…”
Section: B Effect Of Bending Axis Orientation Stress Typesupporting
confidence: 82%
“…Under gate injection, applied tensile ͑compressive͒ stress decreases ͑increases͒ the tunneling barrier height of electrons from gate to substrate via TaN gate work function shift, resulting in an increase ͑decrease͒ in gate leakage current. 15 Under substrate injection, mechanical stress-induced electron repopulation between ⌬ 2 and ⌬ 4 subbands in the n-type inversion layer changes the out-of-plane effective mass and tunneling barrier height of electrons in ⌬ subbands as previously reported. [16][17][18][19] During CVS for thin SiO 2 ͑Ͻ2.5 nm͒, energetic electrons were injected from gate to the Si substrate, breaking dangling bonds in the ͓111͔ direction, normally passivated by hydrogen at P b0 and P b1 centers at near the SiO 2 / ͑100͒Si interface.…”
Section: Impact Of Mechanical Stress On Direct and Trap-assisted Gatementioning
confidence: 61%
“…Meanwhile, the anodic current at the electrode surface can decrease near-surface work hardening and increase the mobility of dislocation, ultimately stimulating fatigue damage [14,15,58]. The strain response of electrode potential or work function has long been of interest in relation to a wide range of problems, including corrosion in structural materials under load [14,[82][83][84] and coupling of electronic properties to stress in semiconductor devices [85,86], and to diffusion [87,88] and metallurgy [89]. Gutman [14] and Sahal et al [84] suggested that the local value of the chemical potential in the liquid/solid system is defined only by the absolute value of the hydrostatic part of the stress tensor, , and is independent of the deviatory part of the stress.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%